Successful treatment of relapsed and refractory CIDP with ofatumumab: a first case report - Wang, Jian; Xiang, QunHong (Frontiers in Immunology, 2024)
Background Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a heterogeneous but treatable immune-mediated neuropathy. Ofatumumab(OFA) is a fully human anti-CD20 monoclonal antibody, has shown promising efficacy in central demyelinating diseases, such as multiple sclerosis (MS). However, there is a lack of studies on the usage of peripheral demyelinating diseases, particularly CIDP. It was presented a case of relapsed and refractory CIDP with an ineffective response to traditional immunotherapy and rituximab(RTX) intolerance but exhibited a positive response to subcutaneous injections of OFA.The patient, a 46-year-old male diagnosed with CIDP, received high-dose intravenous methylprednisolone, intravenous immunoglobulin(IVIG), and plasma exchange(PE) during the acute phase of the disease, During the remission phase, long-term oral administration of prednisone, azathioprine (AZA), and mycophenolate mofetil(MMF) was implemented. Despite this, the patient suffered six relapses over a five-year period, and due to frequent relapses, an ineffective response to conventional immunotherapy and intolerance to RTX, subcutaneous injection of OFA was selected as a prophylactic treatment against relapses. After a total of six injections of OFA, CD19+B cells were substantially depleted. The patient has been followed for more than 23 months without relapses. Conclusions This case demonstrates the effectiveness and fine tolerance of OFA in treating relapsed and refractory CIDP. Further studies are needed to investigate the efficacy and safety of OFA in patients with relapsed and refractory CIDP, especially for those who have shown an ineffective response to traditional immunotherapy and are intolerant to RTX.